Drug interactions of non-vitamin K antagonist oral anticoagulants: inside and outside table cells - Sergey Nikolaevich Bel'diev; Irina Vladimirovna Medvedeva; Dmitry Jur'evich Platonov (Столичная издательская компания, 2017)
The opinion is expressed in some domestic publications that rivaroxaban has the most favorable profile of drug interaction in comparison to other non-vitamin K antagonist oral anticoagulants (NOAC). The basis for such judgments is the summary table of drug interaction from the 2015 practical guide of the European Heart Rhythm Association on the use of NOAC in patients with non-valvular atrial fibrillation.The paper discusses the issue that the above table contains some incorrect qualitative statements and quantitative data inconsistent with primary sources on NOAC drug interactions, and provides the updated and extended information on changes in NOAC plasma concentrations when co-administered with drugs from the other groups. On the basis of the presented data, the authors come to the conclusion that the profile of drug interaction of rivaroxaban does not differ significantly from the other NOAC.